2000
DOI: 10.1054/bjoc.2000.1295
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of paclitaxel, weekly, 24-hour continuous infusion 5-fluorouracil, folinic acid and cisplatin in patients with advanced gastric cancer

Abstract: SummaryTo evaluate the toxicity and efficacy of combination chemotherapy with paclitaxel, cisplatin and 24 h continuous infusion of 5-FU/folinic acid in patients (pts) with unresectable, locally advanced or metastatic gastric adenocarcinoma. Forty-five chemotherapy-naive pts (28 male and 17 female) with a median age of 60 years (range 35-74) were enrolled. 5-FU 2 g/m 2 was given weekly over 24 h i.v. preceded by folinic acid 500 mg/m 2 as a 2 h infusion. Paclitaxel 175 mg/m 2 was administered as a 3 h-infusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
57
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 32 publications
3
57
0
Order By: Relevance
“…An administration schedule at doses of 175-225 mg/m 2 by intravenous infusion every 3 weeks has been widely accepted [9]. In addition, several phase II studies have shown that paclitaxel, alone or in combination with cisplatin or 5-fl uorouracil (5-FU), is also active against advanced gastric cancer [10][11][12][13]. However, a relatively high incidence of grade 3 or 4 neutropenia (14%-35%) is one of the major adverse effects.…”
mentioning
confidence: 99%
“…An administration schedule at doses of 175-225 mg/m 2 by intravenous infusion every 3 weeks has been widely accepted [9]. In addition, several phase II studies have shown that paclitaxel, alone or in combination with cisplatin or 5-fl uorouracil (5-FU), is also active against advanced gastric cancer [10][11][12][13]. However, a relatively high incidence of grade 3 or 4 neutropenia (14%-35%) is one of the major adverse effects.…”
mentioning
confidence: 99%
“…Preliminary data on docetaxel (at a dose of 85 mg m 72 ) combined with CDDP every 3 weeks seem to be promising with a response rate of 56% (Roth et al, 2000). Similarly, Kollmannsberger et al (2000) reported a response rate of 51% combining paclitaxel with CDDP and 5-FU. However, the results obtained with these newer schedules seem to be comparable with those of our regimen.…”
Section: Discussionmentioning
confidence: 96%
“…New cytotoxic agents, such as irinotecan, paclitaxel and docetaxel could be a more appealing approach for the treatment of advanced gastric cancer (Kollmannsberger et al, 2000;Mavroudis et al, 2000;Roth et al, 2000). Docetaxel obtained a 20% response rate as first-line treatment in 37 advanced gastric patients (Sulkes et al, 1994) with a median survival time of 7 months.…”
Section: Discussionmentioning
confidence: 99%
“…The continuing lack of substantial progress in the treatment of advanced gastric cancer, particularly in patients with poor performance status or compromised organ function, who are unlikely to tolerate potentially active but toxic regimens, has prompted investigators to evaluate new agents and/or drug combinations including docetaxel, paclitaxel, and irinotecan (Bokemeyer et al, 1997;Boku et al, 1999;Murad et al, 1999;Kollmannsberger et al, 2000;Roth et al, 2000;Ridwelski et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…It has demonstrated broad clinical activity in a variety of malignancies both alone and in combination regimens. Antitumour activity of paclitaxel also has been shown in gastric cancer cell lines and in several phase I/II trials (Arbuck, 1994;Bokemeyer et al, 1997;Murad et al, 1999;Kollmannsberger et al, 2000;Safran et al, 2000). Paclitaxel is usually well tolerated with myelosuppression being the dose-limiting toxicity and patients receiving this agent can be treated on an outpatient basis.…”
mentioning
confidence: 98%